Predictive validity of body fat percentage by bioimpedance compared with deuterium oxide dilution in Costa Rican schoolchildren - Zamora Alfaro, José Antonio (2017)
OBJECTIVE: The purpose of this study was to verify the validity of body fat percentage (BF%) by bioelectrical impedance analysis (BIA) in a sample of Costa Rican schoolchildren. METHODS: The sample consisted of 52 male (mean age 8.1 ± 0.9 years) and 49 female (mean age 7.5 ± 1.0 years) schoolchildren. Deuterium oxide dilution was the reference method used as the “gold standard” to determine the fat mass (FM) expressed as BF%. Linear regression analyses and paired sample t‐tests were used to test the association and mean differences between BIA and deuterium oxide dilution BF%. Concordance between BIA and deuterium oxide dilution BF% was determined by Lin's concordance correlation coefficient. Measurement of agreement between the two methods was analyzed using the Bland‐Altman procedure. RESULTS: Significant associations between BIA and deuterium oxide dilution BF% were found in males (R = 0.97, R2 = 0.95, P < .0001) and in females (R = 0.98, R2 = .96, P < .0001). The measurements of BF% (mean ± SD) were not significantly different between males (BIA 31.1 ± 7.6% vs. deuterium oxide dilution 31.0 ± 7.4%) and females (BIA 25.9 ± 7.9% vs. deuterium oxide dilution 26.3 ± 7.8%) by t‐test. Lin's concordance correlation coefficient identified an almost perfect strength of agreement between males and females. Bland‐Altman plots showed that the Bodystat measured similar BF% compared to the deuterium oxide dilution in both males and females. CONCLUSIONS: BIA Bodystat presented high agreement with BF% measured by deuterium oxide dilution; therefore BIA Bodystat is recommended for estimating BF% in Costa Rican schoolchildren.